A Quality assessment of education and for Kenya's tour-operating sector - Mayaka, M; King, B (Current Issues in Tourism, 2002)
This study examines the provision of tourism education and training in Kenya in the context of Sub-Saharan Africa and developing countries. Specifically the paper examines the human resource skills needed by Kenya’s tour-operating sector and the extent to which current training provision is adequate. The approach used in the present study is a modified version of WTO’s Tourism Education and Quality (TEDQUAL) methodology. The results indicate considerable convergence between the perceptions of industry operators and education providers concerning quality gaps in the development of skills. A number of systemic training shortcomings are identified including curriculum deficiencies and the inadequate development and enhancement of workplace skills. In view of the resource constraints facing most developing countries, it is argued that tourism trainingandeducation should consciously address the needs of the locally-based industry and that such an approach should result in a more effective education and training system.
KerkoCite.ItemAlsoKnownAs: 10.1080/13683500208667911 10/dkhvf5 2129771:NHULUCSM 2317526:2ZMSW74Z
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Kenya; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:T; D:developing country; F:assessment; P:measurement; P:technology; P:tourism; T:Ausbildung; _C:Algeria DZA; _C:Australia AUS; _C:Canada CAN; _C:Congo XCO; _C:Egypt EGY; _C:France FRA; _C:Ghana GHA; _C:Indonesia IDN; _C:Japan JPN; _C:Kenya KEN; _C:Namibia NAM; _C:Netherlands NLD; _C:New Zealand NZL; _C:Nigeria NGA; _C:Singapore SGP; _C:United States USA; __C:filed:1; __C:scheme:1; publicImportV1